Effect of Change in Macroeconomic Variables on Aggregate Private Investment Growth in Kenya - Mangi, Pato; Troon, Benedict; Ombok, Maurice; Kemboi, Gladys (International Journal of Economics, 2025)
Purpose: Aggregate private investment is key in stimulating economic growth and development of a country such as Kenya. However, the sector seems to be influenced by changes in macroeconomic variables. Therefore, the study aimed at determining the effect of change in macroeconomic variables on aggregate private investment growth in Kenya. It focused on the effect of changes in interest, inflation and exchange rates on aggregate private investment growth in Kenya as the key objectives of the study. Methodology: The study adopted the quantitative causal research design. Secondary data obtained from the World Bank was used, with a time scope of between 1972 and 2023. Data was analyzed through exploratory and inferential analyses via R software. Cointegration analysis was carried out through the Johansen test and both the Maximum Eigenvalue and Trace tests indicated the absence of cointegration relationships since the test statistic values were less than the critical values at ∝ = 0.05. Thus, ARDL estimation technique was adopted. Findings: The study’s findings indicated that change in interest rate had a statistically significant negative effect on aggregate private investment growth in Kenya (P-value < 0.05). Furthermore, the study revealed that such effect wasn’t instant but was translated after three years. The study further found that change in inflation rate had a statistically significant positive effect on Kenya’s aggregate private investment growth (P-value < 0.05). Likewise, such effect was felt on aggregate private investment after eight years. Finally, the study showed that change in exchange rate did not have any significant effect on aggregate private investment growth in Kenya (P-value > 0.05). Unique Contribution to Theory, Practice and Policy: The study recommends the need to manage the changes in macroeconomic variables including inflation and interest rates within their target range as prescribed by the “monetary policy” so as to ensure macroeconomic stability and boost aggregate private investment growth in Kenya.